2017
DOI: 10.1016/j.apmt.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing extraterrestrial regolith material simulants for in-situ resource utilisation based 3D printing

Abstract: This research paper investigates the suitability of ceramic multicomponent materials, which are found on the Martian and Lunar surfaces, for 3D printing (aka Additive Manufacturing) of solid structures. 3D printing is a promising solution as part of the cutting edge field of future in situ space manufacturing applications. This investigation has shown that -provided that the simulants are good matches for the actual regoliths -the lunar material is a viable candidate material for powder bed fusion 3D printing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…These tests proved to be successful and a 3D printer has been permanently installed at the ISS for both emergency part creation and for general component production at the ISS for on-going experiments. In addition to studying small FFF 3D printing, significant research has been conducted in the area of using in-situ materials to create large construction projects off-earth [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…These tests proved to be successful and a 3D printer has been permanently installed at the ISS for both emergency part creation and for general component production at the ISS for on-going experiments. In addition to studying small FFF 3D printing, significant research has been conducted in the area of using in-situ materials to create large construction projects off-earth [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…There are relatively few researches on laser sintering of lunar regolith/simulant -only three research works (Balla et al 2012, Fateri and Gebhardt 2015, Goulas et al 2017 were found. Despite the thermal transient stresses and residual stresses of direct laser sintering of raw lunar regolith (Balla et al 2012), the initial experiments with the lunar simulants, e.g.…”
Section: Laser and Solar Sinteringmentioning
confidence: 99%
“…Despite the thermal transient stresses and residual stresses of direct laser sintering of raw lunar regolith (Balla et al 2012), the initial experiments with the lunar simulants, e.g. 10 x 25 mm cylinder using JSC-1AC (Balla et al 2012), 30 x 30 mm net-shape object using JSC-1A (Fateri and Gebhardt 2015), and 20 x 20 x 5 mm cube using JSC-MARS-1A (Goulas et al 2017), showed that the samples were successfully melted and formed into the desired parts with high geometrical accuracy. Regardless of the interesting results, however, direct laser sintering alone may not be an ideal fabrication method for a construction-scale object for following reasons:  Balla et al (Balla et al 2012) claimed that their method requires low energy, 2.12 J/mm 2 , with a layer thickness of 254 µm, using 50 W of laser power.…”
Section: Laser and Solar Sinteringmentioning
confidence: 99%
“…Apart from the ground environment, the space environment poses severe challenges for metal additive manufacturing technology, including the current heat transfer system, the additive manufacturing process, and heat source equipment [6,7]. Metal wire additive manufacturing technology using a laser beam as a heat source has the advantages of high energy density, high precision, high efficiency, and high flexibility [8,9]. However, in this approach, the device structure is relatively complicated, the power output is high, and the energy utilization rate is relatively low.…”
Section: Introductionmentioning
confidence: 99%